The Correlation between Students Learning Styles and Their English Academic Achievement - Nurhayati, Nurhayati; Penna, Henitha Tabita Deity (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Klabat, 2023)
This study aims to find the correlation between students learning styles and their English academic achievement. This research used quantitative method which involved descriptive (MEAN score) and correlation (Pearson Product Moment Correlation Coefficient) analyses. To gather the data, a questionnaire was used as the instrument to measure the learning styles of the students. This research used a convenience sampling method for the study. This study was conducted at SMA Unklab Airmadidi with 80 respondents from grade X IPA. The result of this study showed that students learning styles were correlated with their English achievement. Keywords— learning styles, English academic achievement